Risk in one is not risk in all: snails show differential decision making under high- and low-risk environments. (August 2022) - Batabyal, Anuradha; Chau, David; Rivi, Veronica; Lukowiak, Ken
Abstract : Predation is a major force that shapes prey phenotypes, species interactions and ecological communities. Prey respond to variation in predation risk and intensity by either increasing or decreasing vigilance and balancing energy requirements under high- or low-risk scenarios. We test the possible mechanism of sensory adaptation and decision making while responding to risk in the pond snail Lymnaea stagnalis . We maintained three risk treatment groups (no risk, low risk and high risk) for 20 days before testing them under multiple cognitive and behavioural challenges involving a predatory stimulus. Under a configural learning procedure where snails learned to forgo feeding when encountering food in the presence of a predatory threat, the high-risk group snails did not show learning/memory formation. However, when high-risk group individuals were transferred to a no-risk environment for 20 days, they were able to form configural learning memory. In a social interaction trial, snails from the no-risk group reduced interactions under threat whereas the high-risk group showed no change between risk environments. All risk groups responded similarly to an operant conditioning training under predation threat that enhanced memory. The decreased antipredator response of the high-risk group in comparison to the low-risk groups shows that snails are able to respond to risk based on past experience, especially when there exists a trade-off between survival and antipredator response. The variation in response to predation threat under different circumstances provides evidence of decision making rather than sensory adaptation as the mechanism involved in prey response. Our study combines multiple phenotypic responses to elucidate animal decision making under different intensities of risk and highlights the importance of experience in shaping antipredator responses. Highlights: We tested snails' responses (sensory adaptation/decision making) to predation risk. Two cognitive tests and one social behavioural assay were used as response. High-risk group animals showed weaker antipredator responses. Response variation across risk groups support a decision-making mechanism at work.